Factors associated with urinary tract infection in the early phase after performing intermittent catheterization in individuals with spinal cord injury: a retrospective study - Xing, Huayi; Dai, Hongyue; Li, Baohua; Yuan, Xiaoning; Liu, Xiaoxuan; Cui, Guoqing; Liu, Nan; Biering-Sørensen, Fin (Frontiers in Medicine, 2023)
Objectives To investigate the occurrence rate of urinary tract infections (UTIs) in the early phase after performing intermittent catheterization (IC) and to explore the possible factors associated with UTIs after performing IC among people with spinal cord injury (SCI). Setting An inpatient rehabilitation department of a teaching hospital in China. Design Retrospective chart review. Methods A retrospective chart review was carried out for traumatic and non-traumatic SCI patients after performing IC during their inpatient stay. Demographic information, comorbidity of diabetes, urine analysis results before IC, method of IC (sterile or clean), use of bladder irrigation, cessation of IC and its reasons, and UTI events were collected. Results A total of 183 adult individuals were included, of which 60 (32.8%) of them were women. The median age was 49.0 years. The median time post-injury was 2 months. The overall occurrence rate of UTI after performing IC was 1.31 (95% confidence intervals: 0.96–1.77) events per 100 days. Sixty-nine (37.7%) patients discontinued IC during hospitalization, and UTIs were the leading reason for cessation (50.7%). Female sex, use of antibiotics for infections other than UTI, and use of bladder irrigation were found to be associated with a lower occurrence rate of UTI in the early phase after performing IC, with an odds ratio of 0.38 (p = 0.019), 0.20 (p = 0.022), and 0.24 (p < 0.001), respectively. Conclusion UTI after performing IC is prevalent among people with SCI. The study indicated that antibiotic prophylaxis and routine bladder irrigation might be associated with the reduction in UTI in the early phase after performing IC. Further research is needed to provide more evidence.